Spirituality of Family in the Philosophy of Abu Ali Ibn Sina - teshayev, nutfullo (Центр Научных Публикаций (buxdu.uz), 2021)
Th the following article, the role of women in the upbringing of children according to the socio-philosophical views of Abu Ali Ibn Sina, the relationship between the man and woman in the family, the characterization qualities of the ideal and the wise woman, the the spiritual-moral upbringing of the child in the family and the personal expression of the parent, the duties and responsibilities of the are mentioned based on the extended sources originating &om the books of the school and the ideas emanated by the contemporary sources